2021
DOI: 10.3892/mmr.2021.12052
|View full text |Cite
|
Sign up to set email alerts
|

Identification of two novel mutations in the PLCD1 gene in Chinese patients with hereditary leukonychia

Abstract: Hereditary leukonychia (HL) is a rare nail dystrophy disease, and several different clinical manifestations and mutations in the phospholipase C δ 1 (PLCD1) gene have been reported. The present study reports on one Chinese family and one sporadic case of with HL. The family members exhibited an autosomal dominant pattern of inheritance with the involvement of all the fingers and toenails in all the patients. Of interest, most of the affected members had koilonychia during their childhood. Thus, the present stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 15 publications
(20 reference statements)
0
6
0
Order By: Relevance
“…Our patient had leukonychia associated with a homozygous missense mutation in the PLCD1 gene. PLCD1, a key enzyme in the cellular signaling pathway, has 15 exons, 1 and is localized and abundant in the human nail matrix using proteomic analysis. 3 …”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Our patient had leukonychia associated with a homozygous missense mutation in the PLCD1 gene. PLCD1, a key enzyme in the cellular signaling pathway, has 15 exons, 1 and is localized and abundant in the human nail matrix using proteomic analysis. 3 …”
Section: Discussionmentioning
confidence: 99%
“…Using genome-wide linkage analysis, Shen et al 1 identified 2 novel mutations in PLCD1 in a Chinese family with HL ( Table I ). All 6 patients (2 males and 4 females) presented with koilonychia in childhood, and 5/6 patients had distal brown discoloration of their nails.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations